2009
DOI: 10.1093/cvr/cvp290
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bilitranslocase in the vascular endothelium and its function as a flavonoid transporter

Abstract: The uptake of some flavonoids into the vascular endothelium occurs via the bilirubin-specific membrane transporter bilitranslocase. This offers new insights into the vascular effects of both flavonoids and bilirubin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…A limited number of studies that have focused mainly on anthocyanins have indicated that bilitranslocase may be involved in vascular epithelial and hepatic flavonoid uptakes and anthocyanin absorption from the stomach (4649). However, the relative importance of bilitranslocase and the identity of other transporters remain to be established.…”
Section: Overview Of Flavonoid Metabolismmentioning
confidence: 99%
“…A limited number of studies that have focused mainly on anthocyanins have indicated that bilitranslocase may be involved in vascular epithelial and hepatic flavonoid uptakes and anthocyanin absorption from the stomach (4649). However, the relative importance of bilitranslocase and the identity of other transporters remain to be established.…”
Section: Overview Of Flavonoid Metabolismmentioning
confidence: 99%
“…This is an unusual finding without clear explanation. In addition to liver, bilitranslocase has been described as present in vascular endothelium, heart, intestinal epithelium, kidney, as well as in plants including carnation petals and grapes (14, 109). The physiological role of bilitranslocase in organic anion transport will require additional clarification.…”
Section: Clearance Of Organic Anions From the Circulationmentioning
confidence: 99%
“…In fact, we have found that a very low concentration of cyanidin 3-glucoside induces nitric oxide-dependent vasorelaxation of rat aortic rings (Ziberna et al, 2011). The enzyme (e-NOS, a synthase) catalysing the formation of nitric oxide is activated by cyanidin 3-glucoside (Xu et al, 2004), which would enter into the cells via bilitranslocase (Maestro et al, 2010). Indeed, pre-treatment of rat aortic rings with purified anti-sequence bilitranslocase antibodies blunted cyanidin 3-glucoside-induced vasorelaxation (Ziberna et al, 2011).…”
Section: The Expression Of Bilitranslocase In the Vascular Endotheliumentioning
confidence: 93%
“…Here, some flavonoids, including malvidin 3-glucoside, have been found to enter into cells via bilitranslocase (Maestro et al, 2010). The vascular endothelium in humans forms a surface of 240 m 2 , thus representing one of the major targets of flavonoids.…”
Section: The Expression Of Bilitranslocase In the Vascular Endotheliumentioning
confidence: 99%